Spectral problem for solvable model of bent nano peapod. Issue 2 (25th January 2017) - Melikhova, A. S.; Popov, I. Yu.
Abstract : The spectral problems for straight and bent chains of weakly coupled conglobate resonators are considered. The band structure of the continuous spectrum is described for the system of straight-type chain. For the bent chain, it is proved that the Hamiltonian has negative eigenvalue for some value of the model parameters and eigenvalues in gaps of the continuous spectrum.